Clinical success of guided tissue regeneration for treating vertical bone and furcation defects in dogs - Lee, Bonnie L.; Soukup, Jason; Rendahl, Aaron; Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2023)
This study evaluated the clinical success rate of guided tissue regeneration (GTR) for treating advanced periodontal disease in a large canine cohort. A total of 112 GTR procedures performed from 2003-2021 were retrospectively evaluated including pre- and posttreatment (3-12 month) periodontal probing depths of 104 treated teeth, dental radiographs of 73 treated teeth, and both diagnostic modalities in 64 treated teeth. Probing depth, radiographically apparent bone height, bone graft material, barrier membrane material, and tooth extraction adjacent to the GTR site were investigated as factors affecting success. Vertical bone defects were evaluated separately from furcation defects. GTR was clinically successful, defined as objective improvement in probing depth, objective decrease in radiographic vertical bone defect, and subjective radiographic gain in bone height, in 90.3% of vertical bone defects. Success was significantly associated with the magnitude of initial probing depth, and type of barrier membrane used. GTR was clinically successful, defined as objective improvement in furcation probing and subjective radiographic improvement of the bone in the furcation, in 22.2% of furcation defects. When F3 lesions were excluded, GTR was successful in 64.3% of furcation defects. GTR is an appropriate treatment to maintain teeth in the oral cavity of dogs with proper client counseling and patient selection but is most likely to be successful in vertical defects.